Sb complexes and Zn interstitials in Sb-implanted ZnO epitaxial films - 刘尧平 英敏菊 梅增霞 李俊强 杜小龙 A．Yu．Kuznetsovc (Chinese physics B, 2011)
In the present work, post-annealing is adopted to investigate the formation and the correlation of Sb complexes and Zn interstitials in Sb-ion implanted ZnO films, by using Raman scattering technique and electrical characterizations. The damage of Zn sublattice, produced by ion bombardment process is discerned from the unrecovered E2 （L） peak in annealed high Sb＋ dose implanted samples. It is suggested that the Zn sublattice may be strongly affected by the introduction of Sb dopant because of the formation of Sbzn-2Vz,, complex acceptor. The appearance of a new peak at 510 cm-1 in the annealed high dose Sb＋ implanted samples is speculated to result from （Zn interstitials-O interstitials） Zni-Oi complex, which is in a good accordance with the electrical measurement. The p-type ZnO is difficult to obtain from the Sb＋ implantation, however, which can be realized by in-situ Sb doping with proper growth conditions instead.